CPR POLICY AND PRACTICE IN AUSTRALIAN RESIDENTIAL AGED CARE FACILITIES (RACFS). Issue 2 (1st June 2013) - Sellars, M; Silvester, W; Fullam, R; Sjanta, R; Jackson, L; Mawren, D; Mountjoy, R
Abstract : Background: International literature suggests current Cardiopulmonary Resuscitation (CPR) policy and practice is highly variable and often ad-hoc in aged care settings. At present, there is no comparable published research on CPR policy and practice in Australian RACFs. Aim: To conduct a national survey on staff knowledge and attitudes, and policies and practices regarding CPR in Australian RACFs. Methods: An online survey was distributed to Australian RACF managers to examine the above. Results: Of 541 RACF managers, only 19% agreed that CPR should be initiated in a witnessed cardiac arrest yet 83% reported that their facility would provide CPR. However, no CPR was administered in 75% of the facilities in the last 12 months and only once in 15%. Only 63% of facilities had a CPR policy and, of these 44% believe that the policy is inadequate. 98% agreed that it is important to discuss resuscitation status with the resident or family, 96% agreed that a resident CPR plan would help to reduce staff uncertainty and 82% supported the introduction of government CPR guidelines. 75% of respondents believed that survival rate of CPR in RACFs is <10% and 35% (correctly) that survival is <2%. Discussion: CPR policy and practice is highly variable between RACFs in Australia, is inconsistent with the recognised outcomes and does not always reflect managerial attitudes and beliefs regarding CPR. Conclusion: The development of a national CPR guideline in Australian RACFs, and provision of education, will assist services in providing consistent and appropriate CPR practices to residents.